Effect of Sodium Ascorbate on Tag Formation in Bleached Enamel - Briso, André Luiz Fraga [UNESP]; Toseto, Roberta Mariano [UNESP]; Rahal, Vanessa [UNESP]; Santos, Paulo Henrique dos [UNESP]; Bovi Ambrosano, Glaucia Maria (Quintessence Publishing Co Inc, 2012)
Purpose: This study analyzed the influence of 10% sodium ascorbate (SA) on tag formation in bleached enamel.Materials and Methods: Five groups were tested: G1 - control; G2 - bleaching with 10% carbamide peroxide (CP) + restoration; G3 - CP + SA + restoration; G4 - bleaching with 35% hydrogen peroxide (HP) + restoration; and G5 HP + SA + restoration. The teeth were sectioned and decalcified, and the resin tags were analyzed at 400X magnification using an optical light microscope and Axiovision software.Results: The mean (SD) resin tag lengths in pm for each group were as follows: G1 - 36.1A (2.5); G2 - 5.8C (2.1); G3 - 14.4B (1.5); G4 - 1.7D (0.7); G5 - 6.5C (2.8). Different letters indicate statistically significant differences.Conclusion: Tooth bleaching with CP or HP impairs the formation of resin tags, and the utilization of sodium ascorbate increases tags length.
Keywords: dental enamel; tooth bleaching; peroxides